The reliability of the modified balance error scoring system - Hunt, T. N.; Ferrara, M. S.; Bornstein, R. A.; Baumgartner, T. A. (Clinical Journal of Sport Medicine, 2009)
The article investigates the intraclass reliability and percent variance that is associated with every component within the traditional Balance Error Scoring System (BESS) protocol. Study shows an intraclass correlation coefficient, having an account for 55% of the total variance. It concludes that when the variance associated with the double-leg stance was removed, the intraclass reliability coefficient of the BESS increased.